Adoption of Preventive Behaviours among General Public in Response to Covid 19 Pandemic - Sunil Kumar Dular; Manisha; Shally; Rekha; Pooja (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current COVID-19 pandemic is unprecedented, but the global response draws on the lessons learned from other disease outbreaks over the past several decades. A new strain of coronavirus which has been emerged recently and was unknown before the outbreak began in Wuhan, China, in December 2019.2 It has been named as NCoV in which ‘n’ is for ‘novel’ and ‘CoV’ is for ‘coronavirus’ that is ‘novel coronavirus’.A total of 52 countries in the world have confirmed cases by 28 February according to WHO data, of which about 94% are in China.5In March 2020, WHO made the assessment and declare the spread of COVID-19 as a pandemic.6 As of 20 April 2020, in India, the Ministry of Health and Family Welfare have confirmed a total number of 17,265 cases, 2,547 recoveries (including 1 migration) and 543 deaths in the country.The aim of the study is to assess the adoption of preventive behaviour among general public in Covid 19 pandemic.To explore the differences in adoption of preventive behaviour regarding Novel Corona Virus among general public and to find out the association of adaptive behaviour with selected demographic variables.In this study a Quantitative approach with pre-experimental descriptive survey design was used. Data was collected among the general public those who are residing in Delhi and Delhi- NCR through google form. a total 459 sample are selected through cluster sampling technique and 4 Point Rating scale were used for the data collection.Result showing that 70% of the subjects were having Good Hygiene behaviour, 88% of the subjects having Good Social Distancing Behaviour and in Health related behaviour 33% are in good, 31% in average, 36% in Poor Behaviour. The Mean and SD of Hygiene related is 20.8± 2.8, social distancing related 18.3±2.5, health related 10.5 ±3.6. In association it is found significant with age, religion and occupation and with others variables it found non-significant.It is concluded that in most of the people were having Good Hygiene related Behaviour and Social Distancing Behaviour but most of the people were having Poor Health related Behaviour. So it is concluded that there is need of improving the health related behaviour among general public.